ChemInform Abstract: Friedel—Crafts Hydroxyalkylation of Indoles Mediated by Trimethylsilyl Trifluoromethanesulfonate. Issue 8 (February 2016) - Downey, C. Wade; Poff, Christopher D.; Nizinski, Alissa N.
Abstract: Friedel‐Crafts silyloxyalkylation of indoles and their subsequent deprotection yield 1:1 adducts of indoles and aldehydes.